Wealth Inequality and the Great Recession - Francesco Bogliacino; Virginia Maestri (Intereconomics, 2016)
The study of wealth and wealth inequality has received far less attention than income, but the increasing importance of wealth, debt and wealth inequality means closer attention must be paid to their concomitant dynamics. Policy interventions to reduce economic inequality continue to target income more than wealth, but targeting the latter – especially through taxes on financial assets – is arguably more effective.
Keywords: 330; Vermögensverteilung; Welt